Synthesis And Identification New Types From * Antimicrobial Polymers And Study Biological Activity - Mutar, Mohammed A.; Hatem, Sara S. (Al-Qadisiyah Journal of Pure Science, 2017)
This research describes the synthesis new Homo polymers and new co-polymers based on synthesis of Oximes as monomers which can synthesized from the reaction of (p-Hydroxyacetophenone , and p-Nitroacetophenone), with Hydroxylamine hydrochloride in presence of NaOH, The Homo polymer was synthesized from the reaction of oxime with each others and formaldehyde in presence of HCl as catalyst,While the co-polymers were prepared from the reaction of oxime with other monomers such as (Toluen sulphonic acid , 2,4-Di chloro benzoic acid) and formaldehyde in presence of HCl as catalyst,These polymers were identified by FT-IR and 1HNMR spectroscopy, The antibacterial,antifungal and antiyeast activities of the synthesized polymers were also screened on various bacteria ,fungal and yeast .All the prepared polymers show excellent antimicrobial activities as compared to the standard ciprofloxacin and amphotericin –B drugs.